AKREDITASI SEKOLAH SEBAGAI JAMINAN MUTU PENDIDIKAN PADA SMA NEGERI 1 DAN 2 PARINGIN - Nabila, Alya; Raihani, Raihani; Yuliani, Yuliani; Aslamiah, Aslamiah; Cinantya, Celia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
SMA Negeri 1 and 2 Paringin are A-accredited schools that have produced competent, excellent, and high-achieving generations of Balangan. Therefore, this research aims to analyze whether the accreditation value truly reflects the real conditions in schools and whether there is a significant relationship between the implementation of accreditation and the improvement of educational quality and overall school performance. This research is qualitative using descriptive research methods. The subjects of the research were leaders, vice principals, and several teachers at SMA Negeri 1 Paringin and SMA Negeri 2 Paringin. The results of the study indicate that both schools have been accredited with better performance in various aspects, graduation rates, student achievements, and active participation in learning activities. It can be concluded that the implementation of accreditation at SMA Negeri 1 Paringin and SMA Negeri 2 Paringin has a positive impact on improving the quality of education, which focuses on continuous improvement, thereby improving performance as seen from increased graduation rates and student achievement.